2016
DOI: 10.1186/s12913-016-1553-9
|View full text |Cite
|
Sign up to set email alerts
|

The care center influences the management of lymphoma patients in a universal health care system: an observational cohort study

Abstract: BackgroundHealthcare providers-related disparities in adherence to the treatment plan among lymphoma patients are found even in a universal healthcare system, but the mechanism remains unclear. We investigated the association between the type of care center and the relative dose intensity and determined whether it persists after adjustment for patients’ recruitment differences.MethodsProspective observational cohort study of 294 patients treated with standard protocols for diffuse large B-cell lymphoma (DLBCL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…However, we did not demonstrate a difference in treatment by residential location, suggesting that some patients residing in non-metropolitan locations may seek treatment in metropolitan centers. This observation is in keeping with other studies suggesting patients treated in community hospitals in less urbanized areas hospitals received lower intensity chemotherapy and less radiotherapy than those treated in university hospitals [4,23]. In Australia, patients living in rural areas are reported to be less likely to receive chemotherapy for advanced stage colorectal cancer [24] however no similar studies in lymphoma have been published to date.…”
Section: Discussionsupporting
confidence: 87%
“…However, we did not demonstrate a difference in treatment by residential location, suggesting that some patients residing in non-metropolitan locations may seek treatment in metropolitan centers. This observation is in keeping with other studies suggesting patients treated in community hospitals in less urbanized areas hospitals received lower intensity chemotherapy and less radiotherapy than those treated in university hospitals [4,23]. In Australia, patients living in rural areas are reported to be less likely to receive chemotherapy for advanced stage colorectal cancer [24] however no similar studies in lymphoma have been published to date.…”
Section: Discussionsupporting
confidence: 87%
“… 37 , 46 More recently, Lamy et al . 47 suggested that even in a universal health care system, disparities in the management of DLBCL patients still exist depending on the type of care center, even after adjustment for differences between patients.…”
Section: Discussionmentioning
confidence: 99%
“…EORTC QLQ-C30 is 1 of the most commonly used PRO measures in oncology clinical trials. 22 It is a multi-dimensional, cancer-specific, evaluative measure of HRQoL. It consists of 30 questions that are scored to create 5 multiitem functional scales, 3 multi-item symptom scales, 6 single-item symptom scales, and a 2-item quality of life (QoL) scale, and uses a 1-week recall period in assessing function and symptoms.…”
Section: Discussionmentioning
confidence: 99%